ANALISIS PENDAPATAN USAHATANI JAGUNG HIBRIDA DI KECAMATAN SEBULU KABUPATEN KUTAI KARTANEGARA - Arista Damayanti; Devit Setiawan (Jurnal Magrobis, 2021)
Along with the roll-out of the Corn Revolution program by the local government of Kutai Kartanegara, it is necessary to conduct research related to the analysis of the hybrid corn business. The research was conducted from October to December 2019, located in Sebulu District, Kutai Kartanegara Regency. The purpose of this study was to determine farm income, R/C ratio and Break Event Point. The types of data in this study are primary and secondary data. The sample in this study amounted to 32 farmers located in Sebulu District, Kutai Kartanegara Regency. This research is included in quantitative research using data in the form of numbers as an analytical tool. The results of the study indicate that the average income is Rp. 23,060,938/farmer/planting season. The average cost incurred is Rp. 6,426,949/farmer/planting season. The average income is Rp. 14,743,943/farmer/planting season and the R/C ratio is 3.58. Break Event Point based on unit is 46,185 kg and BEP price is Rp 1,139.